1989
DOI: 10.1002/j.1460-2075.1989.tb08502.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the RNA polymerases of Trypanosoma brucei: trypanosomal mRNAs are composed of transcripts derived from both RNA polymerase II and III.

Abstract: To analyze transcription in Typanosoma brucei, we have characterized the trypanosomal RNA polymerases. Here we present our results, which allow a discrimination between the different classes of RNA polymerases in nuclear run‐on experiments by polymerase inhibitors and Mn2+ dependence. We also describe the separation of trypanosomal RNA polymerases by chromatography, demonstrating that T. brucei contains RNA polymerases I‐III. The outcome of our experiments suggests that the VSG genes of T. brucei are not trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 48 publications
2
55
2
Order By: Relevance
“…AGTC (41,64). This observation has led to suggestions that VSG genes and PARP genes are transcribed either in the nucleolus along with the rRNA genes (59,75) or by a modified RNA polymerase 11 (26,32). Recently, the promoter for the PARP genes was shown by deletion analyses and linker scanning mutagenesis to encompass about 230 bp immediately upstream of the transcription start site, including a core region and an upstream control element (7,64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGTC (41,64). This observation has led to suggestions that VSG genes and PARP genes are transcribed either in the nucleolus along with the rRNA genes (59,75) or by a modified RNA polymerase 11 (26,32). Recently, the promoter for the PARP genes was shown by deletion analyses and linker scanning mutagenesis to encompass about 230 bp immediately upstream of the transcription start site, including a core region and an upstream control element (7,64).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear run-on assays, coupled with UV inactivation of transcription, have been used to demonstrate that for at least some VSG ESs, transcription is initiated 45 to 60 kb upstream of the VSG gene and proceeds through eight or more open translation reading frames, the last of which specifies the VSG (12,30,37,42,56). This transcription occurs in the presence of ox-amanitin, leading to suggestions that it is catalyzed by an RNA polymerase I activity or by a modified RNA polymerase II complex (26,32,59,75). The resultant polycistronic transcript is processed into the individual mRNAs by 5' trans splicing and 3' polyadenylation.…”
mentioning
confidence: 99%
“…The presence of all three RNAPs in Trypanosoma brucei has been demonstrated by Mono-Q anion exchange chromatography and nuclear run-on experiments with polymerase inhibitors (Grondal et al, 1989), while in Leishmania, they have been separated by a combination of carboxymethyl-sephadex and diethylaminoethyl-sephadex chromatography (Sadhukhan et al, 1997). BLAST analysis of the recently sequenced Leishmania major, T. brucei and Trypanosoma cruzi (Tritryp) genomes (Ivens et al, 2005) revealed the presence of all the shared and homologous subunits, with the exception of RPB12, RPA43 and RPA14/RPB4/RPC9, but most of the RNAP-specific subunits were not identified.…”
Section: Introductionmentioning
confidence: 99%
“…Purified GTases isolated from other sources cap 5'-tri-or -diphosphate RNAs indiscriminately, and the specificity of the capping reaction for Pol II transcripts in vivo is thought to reside within the Pol II transcription initiation complex (6). However, since it has been argued that the SL-RNA is transcribed by Pol III (10), it is unlikely that the capping activity in the kinetoplastid protozoa is limited to the Pol II initiation complex. It is particularly interesting that the apparent specificity of the in vitro T. cruzi activity closely reflects the in vivo capping requirements of the kinetoplastid protozoa.…”
Section: Resultsmentioning
confidence: 99%
“…refs. 7 and 8), and some protein coding genes may not be transcribed by a normal a-amanitin-sensitive Pol 11 (9)(10)(11). Thus, it has been proposed that trans-splicing evolved in the kinetoplastid protozoa as a means of capping protein coding mRNAs (12).…”
mentioning
confidence: 99%